A contrastive analysis of Ibanag and English personal pronouns - Cabasal, Dominador Z. 1931- (1968)
The aim of the study is to discover possible problems of Ibanags learning English personal pronouns through a systematic comparison of the personal pronoun system of the Ibanag and the English language. It specifically describes the nature of the two systems based on three aspects, namely, their contrastive features of form and meaning, their variations, and their distributions.
Vita.
Thesis (M.A. Language Education)--University of the Philippines, Diliman.
Keywords: English language -- Grammar, Comparative and general -- Pronouns; Ibanag language -- Grammar, Comparative and general -- Pronouns